EVALUATION OF THE IMPLEMENTATION OF PUBERTY EDUCATION AND MENSTRUAL HYGIENE MANAGEMENT USING THE OKY APPLICATION - Charisma Destrikasari; Evi Martha (Jurusan Kebidanan Poltekkes Kemenkes Jakarta I, 2026)
Indonesia has a large adolescent population (15.8% aged 10–19 years), making them a strategic group in reproductive health programs. However, knowledge and practices related to puberty and menstrual hygiene management (MHM) remain limited. To address this gap, UNICEF and PKBI introduced OKY, an interactive digital application designed to provide adolescent-friendly menstrual information. This study aimed to evaluate the implementation of puberty and MHM education through the Oky application using the CIPP (Context, Input, Process, Product) evaluation model. A qualitative case study design was conducted in two vocational schools in Jakarta: SMK Negeri 50, which has an active PIK-R, and SMK Muara Indonesia, which no longer has PIK-R. Data were collected through in-depth interviews with program officers, teachers, school principals, focus group discussions (FGDs) with students, and document reviews. Findings showed that the context aligned with adolescents’ need for accessible reproductive health information. Regarding input, collaboration between PKBI and schools was effective, though support varied: SMK Negeri 50 benefited from PIK-R in fostering openness, despite limited counseling teachers, while SMK Muara Indonesia faced challenges of limited staff, facilities, and coordination. In terms of process, both schools adjusted implementation to their conditions, but engagement in planning, monitoring, and evaluation remained limited. For product, both schools demonstrated improvements in knowledge, attitudes, and behaviors, with more significant changes at SMK Negeri 50 due to PIK-R support, whereas SMK Muara Indonesia showed progress but required stronger mentoring. In conclusion, Oky is effective as a digital education tool, yet program sustainability requires strengthened teacher capacity, results-based monitoring, parental involvement, and cross-sectoral policy support.